FREKUENSI PERENDAMAN TIRISAN RUMPUT LAUT SEBAGAI PUPUK CAIR TERHADAP LAJU PERTUMBUHAN DAN PRODUKSI RUMPUT LAUT (KAPPAPHYCUS ALVAREZII) PADA WADAH TERKONTROL - Akmal Akmal; Darmawati Darmawati; Agus Satriyono (Universitas Muhammadiyah Makassar, 2016)
The purpose of this study was to determine the frequency of seaweed soaking liquid seepage towards daily growth rate and production of seaweed Kappaphycus alvarezii. The usefulness of this research is the data and information with seepage benefits of seaweed with a test frequency of immersion. This study was conducted in February to the month of March 2014 in BBAP Takalar, Takalar, South Sulawesi Province, tools and materials used jars, aeration, wearing a green, plastic bag crop thermometer, pH-meter, hand refractometer, Scales, autoclave, sliding bar, knife Kutter, Kappaphycus alvarezii seaweed, seawater, detergent and distilled water. The experimental design used was completely randomized design (CRD) with treatments and 3 replications and 1 control. Treatment A (1 time), treatment B (2 times), the carrying out of the C (3 times), the carrying out of D (control). Testing frequency leakage liquid immersion using seaweed as liquid fertilizer correlated to the growth and production of seaweed daily. The average daily relative growth rate and production are considered to be effective is the treatment C with a frequency of immersion 3 times each (0.0357% / day and 1,5000gr / m2) and lowest in D without soaking treatment (control) respectively (0.0094% / day and 0,3967gr / m2).